2022
DOI: 10.3390/plants11070918
|View full text |Cite
|
Sign up to set email alerts
|

GC/MS Profiling, Anti-Collagenase, Anti-Elastase, Anti-Tyrosinase and Anti-Hyaluronidase Activities of a Stenocarpus sinuatus Leaves Extract

Abstract: Today, skin care products and cosmetic preparations containing natural ingredients are widely preferred by consumers. Therefore, many cosmetic brands are encouraged to offer more natural products to the market, such as plant extracts that can be used for their antiaging, antiwrinkle, and depigmentation properties and other cosmetic purposes. In the current study, the volatile constituents of the hexane-soluble fraction of a Stenocarpus sinuatus (family Proteaceae) leaf methanol extract (SSHF) were analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 79 publications
(88 reference statements)
0
37
0
Order By: Relevance
“…The docking study was conducted to demonstrate the binding affinities of the tested compounds to the active sites of the protein [ 80 , 81 ]. The study was performed using Molecular Operating Environment (MOE 2019.02) software [ 82 , 83 ].…”
Section: Methodsmentioning
confidence: 99%
“…The docking study was conducted to demonstrate the binding affinities of the tested compounds to the active sites of the protein [ 80 , 81 ]. The study was performed using Molecular Operating Environment (MOE 2019.02) software [ 82 , 83 ].…”
Section: Methodsmentioning
confidence: 99%
“…This procedure includes the arrangement of the 3D coordinate space on the binding site of the target, calculation of the binding affinity of the formed complex, and elaboration of the subsequent orientation of a molecule on the ligand’s binding site. The largest magnitude negative number signifies the sensitivity of binding affinity, representing the most satisfactory conformation of the formed complex [ 24 , 25 , 26 , 27 ]. Here, we reveal the isolation and larvicidal activity of two cyclodepsipeptides, scopularide A and B, along with the crude extracts, from the culture rice media of both endophytic A. flavus and A. nomius , isolated from Sarcophyton ehrenbergi .…”
Section: Introductionmentioning
confidence: 99%
“…As with the antioxidant activity mentioned above, these skin aging-related enzyme inhibitory effects of AP plasma treatments are probably due to the polyphenols in peanut shell extract. In previous studies, many anti-aging products were reported in green tea, grape seed, coconut, and argan extracts [ 21 , 25 ]; however, the skin aging-related enzyme inhibitory activities of peanut shell have not yet been elucidated. Recently, many cosmetic companies have shown an interest in natural substances that have anti-tyrosinase, anti-elastase, and anti-collagenase activities.…”
Section: Resultsmentioning
confidence: 99%